OPTIMALISASI LIMBAH ASAL TERNAK DENGAN BIOTEKNOLOGI FERMENTASI MELALUI PEMBERDAYAAN KELOMPOK MASYARAKAT - Gusti Irya Ichriani; Fakhrur Razie; Aditya Dyah Utami (Jurnal Abdi Insani, 2026)
The optimizing quality of marginal lands to support extensification of agricultural requires specific-location improvement strategies.  The application of biomass from fermentation biotechnology has the ability to improve the soil quality. Livestock waste is a potential sources of biomass. On the other hand, the partner has insufficient understanding dan skill in managing waste of their livestock. The quantity of livestock in the partner locations is large. These are required for proper management, especially in terms of feeding, animal health, and waste management, as these factors could impact the quality of livestock. Optimizing the utilization of the livestock waste program is highly relevant and can be enchanced by the appropriate technology application, which will improve the quality of  agriculture and animal husbandry in the area. The aims of these programs are to transfer of biotechnology knowledge and skill for the waste livestock management i.e. composting, bio-urine fermentation, beneficial microorganism application and packaging of these product. This program combined methods such as knowledge sharing, training, application of technology-mentorship and evalution of implementation and sustainability program. The outcomes of the program shown that the partners have understood the importance of livestock waste managing and are capable of processing it independently into compost and bio-urine-enriched functional  microbes. Furthermore, the partners could also have the ability to package their product for marketing purposes.